(untitled) (Journal of the Management Sciences, 2024)
In recent times, the pharmaceutical industry in Nigeria has been faced with challenges such as a shortage of qualified personnel, dwindling performance supply chain disruptions, poor conflict management strategies, ineffective research and development, etc. This study therefore examines the relationship between conflict management and organizational performance in selected pharmaceutical companies in Lagos State Nigeria. The descriptive survey design was used and the population of the study comprised all pharmaceutical companies headquartered in Lagos, Nigeria. Proportionate and random sampling techniques were used to select the sample size of 389 which was determined using Yamane’s (1967) sample size formula. A closed-ended questionnaire was designed and administered through computer-assisted means (Google Form) with a 98% response rate. Findings revealed that the combined effect of both dependent and independent sub-variables revealed that conflict management has a weak positive and insignificant correlation with organizational performance in selected pharmaceutical companies in Lagos State, Nigeria (R = 0.085, p >0.005). The study recommends that the management of pharmaceutical companies in Lagos State, Nigeria, should formulate a comprehensive business policy aimed at implementing a contemporary conflict management approach across all departments, in order to enhance employee morale, it is essential for management to actively foster and endorse interpersonal relationships among colleagues. It is also recommended that investment in improving information and communication technology (ICT) tools should be considered to facilitate efficient and timely communication. By doing so, they would be able to effectively compete with their counterparts in the industry within Africa and globally.